Reducing Perinatal Mortality in India: Two-Years Results of the IRIA Fetal Radiology Samrakshan Program - Rijo M. Choorakuttil; Bavaharan Rajalingam; Shilpa R. Satarkar; Lalit K. Sharma; Anjali Gupta; Akanksha Baghel; Neelam Jain; Devarajan Palanisamy; Ramesh Shenoy; Karthik Senthilvel; Sandhya Dhankar; Kavita Aneja; et al. (Indian Journal of Radiology and Imaging, 2022)
Aim The aim of the study is to determine improvements in perinatal mortality at the end of the first 2 years from the initiation of the Samrakshan program of the Indian Radiological and Imaging Association. Methods Samrakshan is a screening program of pregnant women that uses trimester-specific risk assessment protocols including maternal demographics, mean arterial pressure, and fetal Doppler studies to classify women as high risk or low risk for preterm preeclampsia (PE) and fetal growth restriction (FGR). Low dose aspirin 150 mg daily once at bedtime was started for pregnant women identified as high risk in the 11–136/7 weeks screening. The third-trimester screening focused on the staging of FGR and protocol-based management for childbirth and risk assessment for PE. Outcomes of childbirth including gestational age at delivery, development of PE, and perinatal mortality outcomes were collected. Results Radiologists from 38 districts of 16 states of India participated in the Samrakshan program that screened 2,816 first trimester, 3,267 second trimester, and 3,272 third trimester pregnant women, respectively. At 2 years, preterm PE was identified in 2.76%, preterm births in 19.28%, abnormal Doppler study in 25.76% of third trimester pregnancies, and 75.32% of stage 1 FGR delivered at term. The neonatal mortality rate was 9.86/1,000 live births, perinatal mortality rate was 18.97/1,000 childbirths, and maternal mortality was 58/100,000 live births compared with 29.5, 36, and 113, respectively in 2016. Conclusion Fetal Doppler integrated antenatal ultrasound studies in Samrakshan led to a significant reduction in preterm PE rates, preterm birth rates, and a significant improvement in mean birth weights. Perinatal, neonatal, and maternal mortality rates are significantly better than the targets for 2030 set by the Sustainable Development Goals-3.